Water dripper hydroponic product thriv / Nur Zulaikha Mohd Zahiruddin - Mohd Zahiruddin, Nur Zulaikha (Universiti Teknologi MARA, Kedah, 2024)
Water drippers are a common component in hydroponic systems. They deliver precise amounts of water and nutrients directly to plant roots, promoting efficient growth and reducing water waste. In Thriv system, water travels through the holes, then sliding down through slide that is connected to the two pots with the plants. These water dripper release the water and nutrient solution, allowing for optimal absorption by the roots. This product was designed to be effortless and simple for the user, the user only needs to place washed fruits/vegetables into the bowl as the water will drip itself, sliding through the roots. It is also age friendly based on the usage and design. With the artsy style, it creates a visual appeal to the environment around.